Aleksander Dubiński (1924–2002), on the 20th anniversary of his death - Dubiński, Adam J. (Vilnius University Proceedings, 2024)
The aim of the article is to present the profile and professional path of Aleksander Dubiński (1924–2002) on the twentieth anniversary of his death. A long-time researcher at the Institute of Oriental Studies at the University of Warsaw and a student tutor, he was interested in many aspects of turcological knowledge, with a particular emphasis on research on the culture of the Karaim minority and Lithuanian-Polish Tatars. The article also discusses the Oriental book collection and periodicals left by Aleksander Dubiński.
Keywords: Aleksander Dubiński; Karaims; Karaites; Karaim language; Karaim studies; Tatar studies